2023
DOI: 10.3389/fonc.2023.1043753
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the retroperitoneal laparoscopic adrenalectomy versus transperitoneal laparoscopic adrenalectomy for large (≥6cm) pheochromocytomas: A single-centre retrospective study

Abstract: ObjectivesTo compare the efficacy and safety of retroperitoneal laparoscopic adrenalectomy (RLA) and transperitoneal laparoscopic adrenalectomy (TLA) in the treatment of large (≥6cm) adrenal pheochromocytomas.MethodsWe retrospectively collected the clinical data of 130 patients with large pheochromocytoma who underwent RLA or TLA in our hospital from 2012 to 2022. The perioperative parameters and follow-up outcomes of the two groups were compared, and univariate and multivariate analyses were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…These lesions were both pheochromocytomas on histopathology, with one only diagnosed post-operatively. The higher PRA pheochromocytomas-related conversion rates observed in this study contradicted findings reported by Hisano M et al [ 28 ] and Lei K et al [ 29 ]; this could be due to bias, given this study's low overall conversion rate. Some studies have suggested that the measurement of retroperitoneal fat mass in preoperative CT can predict conversion rate [ 30 ].…”
Section: Discussioncontrasting
confidence: 90%
“…These lesions were both pheochromocytomas on histopathology, with one only diagnosed post-operatively. The higher PRA pheochromocytomas-related conversion rates observed in this study contradicted findings reported by Hisano M et al [ 28 ] and Lei K et al [ 29 ]; this could be due to bias, given this study's low overall conversion rate. Some studies have suggested that the measurement of retroperitoneal fat mass in preoperative CT can predict conversion rate [ 30 ].…”
Section: Discussioncontrasting
confidence: 90%
“…The application of RLA for managing LATs remains a challenging and contentious topic. Lei et al (14) and Shiraishi et al (15) shared their experiences using TLA and RLA to treat large pheochromocytomas. Their findings demonstrated that RLA was superior to TLA, yielding reduced operation time, less EBL, quicker time to ambulation, earlier time to oral intake, and shorter hospital stays (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al (14) and Shiraishi et al (15) shared their experiences using TLA and RLA to treat large pheochromocytomas. Their findings demonstrated that RLA was superior to TLA, yielding reduced operation time, less EBL, quicker time to ambulation, earlier time to oral intake, and shorter hospital stays (14,15). This aligns with the outcomes highlighted in the aforementioned systematic review (9,13).…”
Section: Discussionmentioning
confidence: 99%